Analysis of Questionnaire Surveys Conducted in Higher Education Institutions from the Perspective of the Institutional Research for Teaching and Learning - Yoshioka Tsuyoshi; Morikura Yusuke; Kobayashi Ryo; Teruya Kensaku; Izumi Toshiro (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study proposes a simplified Customer Satisfaction (CS) analysis procedure by summarizing the CS analysis method, which can be practically applied to questionnaire analysis from the perspective of Institutional Research for Teaching and Learning (IRTL). Most of the questionnaire surveys conducted in higher education institutions are mere aggregations of the percentage of responses. A course evaluation questionnaire assessment method applying CS analysis, which is often used in marketing, has already been established to solve this problem. However, this method cannot be practically implemented if IRTL organizations are not fully functional. Using this proposed method, it is possible to specifically analyze the items that need to be focused on and improved to enhance student satisfaction. Furthermore, this study also examines whether the proposed method could be applied to the analysis of questionnaires for student surveys that have been conducted in recent years. As a result, the proposed method based on the perspective of IRTL has also succeeded in summarizing the guidelines for higher education institutions to conduct survey analysis.